Active methodologies, focusing on teaching and learning processes (Research, Society and Development, 2020)
The present work aims to analyze publications on the topic of the so-called Active Methodologies, focusing on Teaching and Learning Processes, through a bibliographic research carried out using data found in the periodicals portal, in the period from 2017 to 2020 With regard to access to references and knowledge bases, after the modernization of the use of technology, the CAPES access portal has become a tool of fundamental importance for research, enabling the democratization of access to information without differentiating regions and institutions. The research addresses a Systematic Review which consists of a secondary study with a well-defined methodology as a process of selecting, evaluating, synthesizing and reporting the evidence. [Kitchenham and Charters, 2007]. This work was carried out using the following descriptors, with and without quotes: Active Methodologies, Benefits and Harm; The most used types of active methodologies; The Importance of Active Methodology; the essence of this type of methodology and the teacher's role in this process was sought. It is important to highlight that the researched works were carried out by authors individually or in pairs. Twenty articles were found in total, with only five relevant for this work. The bibliographic research indicated that the active methodologies are of great importance for the construction of a new education, which aims at the construction of critical thoughts, the formation of a leader, the performance of group activities and the link that is created between the teacher and the student.